Inhibition of extracellular signal-regulated kinase potentiates the apoptotic and antimetastatic effects of cyclin-dependent kinase inhibitors on metastatic DU145 and PC3 prostate cancer cells - Çoker Gürkan, Ajda; Ünsal, Zeynep Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; RENCÜZOĞULLARI, ÖZGE (Wiley Online Library, 2018)
Purvalanol and roscovitine are specific cyclin‐dependent kinase (CDK) inhibitors,which have antiproliferative and apoptotic effects on various types of cancer.Although, the apoptotic accomplishment of purvalanol and roscovitine waselucidated at the molecular level, the underlying exact of drug‐induced apoptosisthrough mitogen‐activated protein kinase (MAPK) signaling still speculative. Inaddition, the role of CDK inhibitors in thedownregulation of extracellular signal–regulated kinase 1/2 (ERK1/2)‐mediated epithelial‐mesenchymal transition (EMT)remains unclear. Here, we investigated the potential effect of each CDK inhibitors oncell proliferation, migration, and generation of reactive oxygen species due to theinhibition of MAPKs in metastatic DU145 and PC3 prostate cancer cells. Wereported that purvalanol and roscovitine induced mitochondria membrane potentialloss–dependent apoptotic cell death, which was also characterized by activation ofseveral caspases, cleavage of poly (ADP‐ribose) polymerase‐1 in DU145 and PC3cells. Cotreatment of either purvalanol or roscovitine with ERK1/2 inhibitor, U0126,synergistically suppressed cell proliferation, and induced apoptotic action. Also,ERK1/2 inhibition potentiated the effect of each CDK inhibitor on the down-regulation of EMT processes via increasing the epithelial marker and decreasingmesenchymal markers through reduction of Wnt signaling regulators in DU145 cells.This study provides biological evidence about purvalanol and roscovitine haveapoptotic and antimetastatic effects via MAPK signaling on prostate cancer cell byactivation of GSK3βsignaling and inhibition of phosphoinositide‐3‐kinase/AKT(PI3K/AKT) pathways involved in the EMT process.
Keywords: apoptosis; epithelial‐mesenchymal transition (EMT); extracellular signal–regulated kinase 1/2(ERK1/2); purvalanol; roscovitine